THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH LENGTH OF WORK AS A MODERATING VARIABLE AT PT.GOTONG ROYONG JAYA MENDARIS - Jopinus Saragih (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to determine the effect of work motivation on employee performance with length of service as a moderating variable at PT. Mutual Cooperation Jaya Mendaris. In this research, data was collected using a questionnaire method from 48 respondents, employees of PT. Gotong Royong Jaya Mendaris Maintenance Department using the census method. Then analysis was carried out using descriptive analysis methods. Namely including validity and reliability tests, classical assumption tests, hypothesis testing via the t test and analysis of the coefficient of determination (R2). The data analysis technique used is multiple linear regression analysis using the Absolute Difference Test which functions to prove the research hypothesis. Data that have met the validity test, reliability test and classical assumption test are processed to produce the following regression equation: Y = 6.439 + 1.328X - 0.244Z. With 1 Independent Variable, 1 Dependent Variable and 1 Moderating Variable, it shows that. Hypothesis 1 states that work motivation has a positive effect on employee performance. From table 4.15, the tcount value is 3.416. With α = 5%, ttable (5%; nk = 46), the ttable value is 2.013. From this description it can be seen that tcount (3.416) > ttable (2.013), likewise with a significance value of 0.001 < 0.05, it can be concluded that the first hypothesis is accepted, meaningthe work motivation variable (X) has an effecton employee performance variables (Y). Hypothesis 2 states thatthe length of work variable (Z) has no effecton employee performance variables (Y). From table 4.15, the tcount value is -0.743. With α = 5%, ttable (5%; nk = 46), the ttable value is -2.013. From the description it can be seen that tcount (-0.743) > ttable (-2.013), and the value The significance is 0.461 > 0.05, so it can be concluded that the second hypothesis is rejected, meaningthe length of work variable (Z) has no effecton employee performance variables (Y). Meanwhile, hypothesis 3 states that the Length of Work Variable (Z) cannot moderate the influence of the Work Motivation Variable (X) on the Employee Performance Variable (Y). From table 4.16, a value of -0.629 is obtained. With a significance value of 0.532 > 0.05, the parameter coefficient value is negative but not significant. Where it can be concluded that the third hypothesis is rejected.